산업용 고구마 개발을 위한 유전자원 현황 및 전망 - 목일진(Il Gin Mok); 자오동란(Dong Lan Zhao); 곽상수(Sang Soo Kwak) (Journal of plant biotechnology, 2009)
In many countries including China and U.S., researchers are developing methods to use sweetpotato as raw material for biofuel. We consider the sweetpotato is not only a source of green fuel, it eventually will provide various material including paper, adhesives, biodegradable plastics, and secondary metabolites. Sweetpotato is one of the high efficiency crop because it yields more calories per unit area than either maize or potato, and it requires the shortest growing cycle of the root crops grown in the tropics. Sweetpotato is the most useful crop for the coming starchbased industry era. Sweetpotato genetic resources are collected, characterized, evaluated, and maintained by U.S., China, Japan, and the International Potato Center. New varieties of sweetpotato using the proper genetic resources and molecular breeding will be developed to cope with the global food and energy in 21st century.